Behavioral and Biochemical Effects of KXS on Postmyocardial Infarction Depression - Hu, Yuan; Liu, Xu; Zhang, Tianyi; Chen, Chao; Dong, Xianzhe; Can, Yan; Liu, Ping (Frontiers in Pharmacology, 2020)
Background: Depression and coronary heart disease (CHD) often occur together in clinical practice. As a traditional Chinese medicine, Kai Xin San (KXS) has been widely used for the treatment of emotion related disorders. In the present study, we aimed to explore whether KXS had both antidepressive effects and cardioprotective functions in a rat model of myocardial ischemia (MI) with depression. Methods: A total of 50 SD rats were randomly assigned into five groups as follows: normal control (control group), celiac injection of isopropyl adrenaline (ISO) (MI group), depression (depression group), MI+ depression (model group) and MI+ depression treated with intragastric administration of 370 mg/kg KXS (KXS group). MI was induced by subcutaneous injection of 85 mg/kg ISO. Depression was developed by a 7-week chronic mild stress (CMS) challenge. Behavioral test was conducted before and during the experiment. Echocardiography and biochemical analysis were carried out after 7 weeks of CMS challenge. Results: After 7 weeks of experiment, depression-like behaviors were observed in all the groups except for control and KXS groups, and KXS treatment dramatically increased open-field test scores and sucrose consumption (P<0.01 vs. model group). Echocardiography and biochemical analysis showed that KXS treatment could improve levels of ejection fraction (EF) and fractional shortening (FS), which were reduced by depression and ISO challenge. Meanwhile, KXS treatment significantly decreased the levels of creation kinase MB (CK-MB) and lactate dehydrogenase (LDH), which were increased in the model group. The activities of superoxide dismutase (SOD), glutathione peroxidase (GSH-PX), catalase (CAT) were increased, while the malondialdehyde (MDA) activity was significantly decreased in the KXS group. Moreover, KXS treatment reduced the levels of C-reactive protein (CRP), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) in myocardial tissue compared with the model group. Conclusions: KXS had antidepressant-like activity and offered cardioprotective effects against ISO-induced myocardial infarction with depression.